Crisis of the Modern Age and the Way Out: An Examination of T. S. Eliot’s Four Quartets - Fatima Falih Ahmed Al-Badrani; Abdullah Fawaz Al-Badarneh (European Scientific Journal, ESJ, 2016)
The twentieth century was one of change and unrest. What characterises the age is that society, up to a high degree, was hostile to spiritual life. The spiritual values seemed to be neglected or totally abandoned for the material, more matter-of-fact values. This left society in a state of increasing confusion that was substantially realised in the outbreak of World War I. The impact of the war revealed the degeneration of the modern world with the breakdown of religion and moral and spiritual traditions. T. S. Eliot was fully aware of the ills of modern civilisation that surrounded people with a number of faiths established haphazardly to fight against the troubles of modern life. These faiths refer to political and social ideologies, parties, and allegiances. Eliot finds that all modern ideologies are poor and futile substitutions for religious faith. He finds that society should be built not upon power and its corruption, but upon a higher system of values which are mainly spiritual and moral. This research paper demonstrates how Eliot's Four Quartets affirms the possibility of spiritual regeneration and gives a positive projection of hope. The central theme of the poem is that if the heart of the individual is ever to be at rest, if his/her tormented apprehension about the transience of human life is ever to be calmed, it will be so when he/she accepts the conviction that humans’ peace is in God's will.